Competence Approach in the Scientific Paradigm of Russian Education - Ulyanina O.A (Moscow State University of Psychology and Education, 2018)
The article analyzes the essence and content of the competence approach in education from the position of domestic researchers. The stages of formation and development of the indicated approach are described: the first stage of categorically-conceptual uncertainty; the second stage of the existence of multiple interpretations of key categorical units and the blurring of the boundaries of concepts competence / competence; the third stage of legal consolidation of the above-mentioned concepts at the state level. The necessity of changing the educational paradigm is substantiated, the existing problems in the preparation of specialists competitive on the labor market are noted. The circle of unresolved questions in the competence approach and the ambiguity of the interpretations of its key conceptual units are outlined. In this connection, the existing views of the scientific community are being studied both on the correlation of the concepts of competence / competence and on their content characteristics. Based on the examination of existing approaches, it is concluded that competence is a systemic concept, as an important new formation of the individual, which arises in the course of training and the subsequent development of professional activity, and competence as its component. Through the prism of the description of the categorical-conceptual apparatus of the competence approach, its conceptual positions in the theory and practice of modern education and training of personnel are examined.